EMHA AINUN NADJIB'S RELIGIOUS HUMANISM AND ITS ROLE FOR RELIGIOUS MODERATION OF MUSLIMS - Maulana, Wildhan; Azizah, Faradila (Proceeding of International Conference on Islamic Education (ICIED); Vol 6 No 1 (2021): Proceeding of International Conference on Islamic Education (ICEID), 2021)
Entering this era of disruption, Muslims are faced with various new paradigms, both spiritual and non-spiritual, so it is feared that they can erode the essence of Islam and local wisdom that has existed before. Responding to this phenomenon, religious moderation continues to be encouraged to strengthen the understanding of religious values ​​as a protector from the influence of destructive ideas. In this context, Emha Ainun Nadjib is a figure who calls for religious moderation through a religious humanism approach. This study aims to provide insight into the role of Emha's religious humanism in Islamic moderation based on Nicola Abbagnano's framework of humanism. While this research is included in the category of library research and uses a descriptive qualitative approach. Emha further explained that the internalization of the Islamic moderation principle can be done through a religious humanism approach by considering socio-cultural factors, demographics, and the level of religious understanding of the people who tend to be different. Therefore, Emha's religious humanism carries three main themes, (1) liberation as an effort to reconstruct a meaningful religious life in the context of empowering human values. (2) Naturalism is the integration of religious understanding that includes theological and sociological dimensions as a result of human contemplation of the essence of religious values. (3) Tolerance among others is a must for Muslims based on a sense of ukhuwah, egalitarianism, and togetherness as part of the structure of the cosmos.